Analisis Penerapan Sistem Kesehatan dan Keselamatan Kerja Pada PT KTC Coal Mining & Energy Site Loa Tebu : Pendekatan Deskriptif Kualitatif Berbasis Data Sekunder - Cabelita Wujianti; Wilda Yanti (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2026)
According to data form ILO, the coal mining industry accounts for approimalety 2.78 million deaths annually, and in 2023, BPJS Ketenagakerjaan reported 2,137 cases in the mining sector. This study aims to analyse the implementation of Occupational Health and Safety (OHS) at PT KTC Coal Mining & Energy using a descriptive qualitative approach with secondary data obtained from the company’s internal documents. The results indicate that the company has effectively implemented its OHS Management system. This is evident through the management’s commitment to achieving “Zero Accident”, as well as the application of hazard identification and risk control in major mining activites using the HIRARC method. In addition, the company provides adequate personal protective equipment and has established emergency response procedures through an Emergency Response Team (ERT) and regular drill simulations. Although most risks are categorized as low to moderate and supported by regular audits, certain challenges remain, such as difficulties in supervision due to the vast working area. Overall, the implementation of OHS in company complies with Government Regulation No. 50 of 2012 and the Mining Safety Management System (SMKP), supported by a collaborative safety culture among employees